PELATIHAN PEMBERDAYAAN PENDAMPING ABK (ANAK BERKEBUTUHAN KHUSUS) DI MADIUN (Eduscotech, 2022)
The Empowerment Training for Children with Special Needs (ABK) Companions in Madiun was conducted to enhance the skills and understanding of companions in providing optimal support for children with special needs. Children with special needs require specific educational approaches to support their physical, emotional, and social development. In this context, companions play a vital role both in school and home environments in facilitating inclusive education processes.This training focused on developing companions’ competencies in adaptive teaching techniques, effective communication strategies, and the creation of supportive learning environments for children with special needs. The program consisted of theoretical sessions and practical activities designed to increase participants’ understanding of common developmental disorders, such as autism, dyslexia, and attention deficit disorders. Participants were also trained to apply practical strategies to help children overcome challenges in learning and social interaction.The results of this training are expected to improve the quality of interaction between companions and children with special needs and to contribute positively to the children’s overall development. By strengthening companions’ knowledge and practical skills, this program supports more effective assistance for children with special needs, enabling them to achieve greater independence and reach their full potential in education and daily life.